The Investigation of Levels of Paraoxonase (PON 1) and Malondialdehyde in Smokers - Gürsu, M. Ferit; Özdin, Mehmet (Fırat University, 2002)
Aim: Present study was aimed to examine relationship between the levels of MDA, end of products of lipid peroxidation, and paraoxonase (PON 1) which prevents development of atherosclerosis activity levels in smokers. Materials and Methods: Sera from total of 49 male subjects aged between 45±5 years (22 chronic smokers, 27 controls) were used in the study.To determine serum paraoxonase activity, paraoxon was used as substrate. Findings: PON activity and concentrations were found to be statistically lowered (p

Amaç: Bu çalışmada kronik sigara içen kişilerde, sigara içiminin lipit peroksidasyonunun son ürünlerinden biri olan malondialdehit (MDA) düzeyleri ile ateroskleroz gelişimini önleyen paraoksonaz (PON 1) aktivite düzeyleri arasındaki ilişkiyi araştırmak amaçlanmıştır. Gereç ve Yöntem: Çalışma ortalama 45±5 yaşlarındaki kronik sigara içici 22 ile hiç sigara içmemiş 27 erkek bireyden oluşan kontrol grubu olmak üzere toplam 49 kişide yapılmıştır. Serum PON aktivitesi ölçümünde paraoxon substrat olarak kullanılmıştır. Bulgular: Sigara içenlerde PON aktivite ve konsantrasyonu istatistiksel olarak anlamlı düşme gösterirken (P
SİGARA İÇENLERDE SERUM PARAOKSONAZ (PON 1) AKTİVİTELERİ İLE MALONDİALDEHİT DÜZEYLERİNİN ARAŞTIRILMASI